Структура просторової інформації в автоматизованих земельно-кадастровых системах - Гавриленко, Дмитро (Видавництво Національного університету «Львівська політехніка», 2009)
The structure of storage and interaction of the spatial information for information land cadastre systems is offered. It is based on models which built taking into account legislation of the Ukraine and experience in administration of the state land cadastre.
Keywords: land cadastre system; objects; boundary; geometry; structure; UML; class